2020
DOI: 10.1136/flgastro-2020-101412
|View full text |Cite
|
Sign up to set email alerts
|

Important relation between self-efficacy, sense of coherence, illness perceptions, depression and anxiety in patients with inflammatory bowel disease

Abstract: IntroductionAnxiety and depression are common disturbances in patients with inflammatory bowel diseases (IBD), and were found to impact the disease course. Illness perceptions (IPs), self-efficacy (SE) and sense of coherence (SOC) are important psychological functions, used by the individual to cope with his chronic disease.Aimsto investigate the association of IP, SE and SOC on anxiety and depression among patients with IBD.Patients and methodsPatients filled questionnaires including: demographic, socioeconom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Coherently with the general findings of this study, the literature suggests that there is a significant and positive relationship between both concepts: the greater the SOC, the greater the ASAS [ 70 , 71 ]. Moreover, the sense of coherence was found to positively impact one’s motivation for self-care [ 31 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 80%
“…Coherently with the general findings of this study, the literature suggests that there is a significant and positive relationship between both concepts: the greater the SOC, the greater the ASAS [ 70 , 71 ]. Moreover, the sense of coherence was found to positively impact one’s motivation for self-care [ 31 , 72 , 73 ].…”
Section: Discussionsupporting
confidence: 80%
“…11,13,17,19,20,22,24,28, Almost all studies were conducted in a single country, with the exception of a multi-national survey including 33 countries. 79 Eleven studies recruited unselected patients with IBD, 45,48,55,57,62,77,83,90,97,102,103 of which one study reported prevalence of symptoms of anxiety or depression for patients with UC or CD separately, five studies recruited only patients with UC, 40,41,49,65,79 and four studies only patients with CD. 46,53,61,101 No study recruited only patients with IBD-U, and none of the included studies reported prevalence of symptoms of anxiety or depression for patients with IBD-U separately.…”
Section: Resultsmentioning
confidence: 99%
“…19,67 Of the 75 studies reporting the prevalence of symptoms of depression in patients with IBD, 44 administered the HADS. 11,13,17,24,28,[37][38][39]41,43,44,45,47,[50][51][52]55,57,59,61,[63][64][65]68,[70][71][72]76,78,80,81,83,84,86,90,92,93,95,96,98,[99][100][101]103 The pooled prevalence of symptoms of depression in these studies was 21.6% (95% CI 18.4% to 24.9%; I 2 =96%, p<0.001). Among the remaining articles that used different questionnaires, the lowest pooled prevalence was reported in three studies using the Zung self-rating depression scale (21.0%; 95% CI 6.9% to 40.1%), 19,…”
Section: Pooled Prevalence Of Symptoms Of Anxiety and Depressionmentioning
confidence: 99%
“…Data from the Middle East are very limited on this topic with only few studies reporting rates of depressive and anxiety symptoms in IBD patients. A study from Israel on IBD patients reported depression rate of 9.36% and anxiety rate of 23.4% 10 . Another study from Iran found that anxiety, depression and psychological stress were highly frequent in UC patients with rates of 29.2%, 40%, and 38.3%, respectively 11 .…”
Section: Introductionmentioning
confidence: 99%